The effects of online customer reviews and online customer ratings on purchasing intentions in west java marketplaces - Naomi, Intan Prilia; Ardhiyansyah, Andri (Faculty of Economics and Business Mulawarman University, 2021)
Technological developments are overgrowing; one of the technologies that are developing is the internet. Technological advances from the internet have led to changes in consumer lifestyles; the changes referred to are consumers who are interested in online shopping activities. However, online shopping is significantly different from offline shopping, where consumers cannot directly assess the product to be purchased. This difference is also a risk for potential consumers when shopping online. So to get information about the product that will be purchased, prospective consumers will use online customer reviews and online customer ratings in the marketplace. This study aims to determine whether online customer reviews and online customer ratings affect buying interest in the marketplace in West Java, either partially or simultaneously. The sample was determined by the non-probability sampling method with 140 respondents and using multiple regression analysis. Based on the study results, it is known that online customer reviews and online customer ratings have an effect of 56.8% on buying interest.